Determination of material constants of vertically aligned carbon nanotube structures in compressions. (19th June 2015) - Li, Yupeng; Kang, Junmo; Choi, Jae-Boong; Nam, Jae-Do; Suhr, Jonghwan
Abstract Different chemical vapour deposition (CVD) fabrication conditions lead to a wide range of variation in the microstructure and morphologies of carbon nanotubes (CNTs), which actually determine the compressive mechanical properties of CNTs. However, the underlying relationship between the structure/morphology and mechanical properties of CNTs is not fully understood. In this study, we characterized and compared the structural and morphological properties of three kinds of vertically aligned carbon nanotube (VACNT) arrays from different CVD fabrication methods and performed monotonic compressive tests for each VACNT array. The compressive stress–strain responses and plastic deformation were first compared and analyzed with nanotube buckling behaviours. To quantify the compressive properties of the VACNT arrays, a strain density energy function was used to determine their intrinsic material constants. Then, the structural and morphological effects on the quantified material constants of the VACNTs were statistically investigated and analogized to cellular materials with an open-cell model. The statistical analysis shows that density, defect degree, and the moment of inertia of the CNTs are key factors in the improvement of the compressive mechanical properties of VACNT arrays. This approach could allow a model-driven CNT synthesis for engineering their mechanical behaviours.